Numerical study of finned type heat exchangers for ICEs exhaust waste heat recovery - M. Hatami; D.D. Ganji; M. Gorji-Bandpy (Case Studies in Thermal Engineering, 2014)
In this paper, two cases of heat exchangers (HEXs) which previously were used in exhaust of internal combustion engines (ICEs) are modeled numerically to recover the exhaust waste heat. It is tried to find the best viscous model to obtain the results with more accordance by experimental results. One of the HEXs is used in a compression ignition (CI) engine with water as cold fluid and other is used in a spark ignition (SI) engine with a mixture of 50% water and 50% ethylene glycol as cold fluid. As a main outcome, SST k–ω and RNG k–ε are suitable viscous models for these kinds of problems. Also, effect sizes and numbers of fins on recovered heat amount are investigated in various engine loads and speeds.